The Influence Of Fintech And Digital Financial Services On Financial Inclusion Among Generation Z At Telkom University - Rahadian, Dadan; Multarida, Nieda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Financial Technology (FinTech) in the field of finance is currently being embraced by all segments of society, including Generation Z. This study aims to examine the influence of Financial Technology and Digital Financial Services on Financial Inclusion. Financial Technology and Digital Financial Services are investigated based on several factors, including Behavioral Intention (BI), Social Influence (SI), Service Trust (ST), and Usability (UB). The research employs a quantitative research method, collecting data through questionnaires. The study population consists of students from Telkom University, particularly those from the 2019 to 2022 cohorts, belonging to the Generation Z category. The sample size for this study is 400 respondents. The collected data is analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM), utilizing the software SmartPLS 3. The factors that serve as the approach for FinTech and Digital Financial Inclusion in this research are interconnected with each other. Therefore, the results of this study demonstrate that FinTech and Digital Financial Institutions have a positive and significant influence on Financial Inclusion.